Early-life Stress Modifies the Reactivity of Neurons in the Ventral Tegmental Area and Lateral Hypothalamus to Acute Stress in Female Rats. (10th May 2022) - Gugula, Anna; Trenk, Aleksandra; Celary, Aleksandra; Cizio, Katarzyna; Tylko, Grzegorz; Blasiak, Anna; Hess, Grzegorz
Highlights: Early life stress (ELS) is a risk factor of substance abuse and mental disorders. Ventral tegmental area (VTA) and lateral hypothalamus (LH) control motivation. ELS enhances c-Fos expression in VTA of female rats in a region specific manner. Morphology of VTA neurons is changed by ELS. ELS alters stress reactivity of dorsomedial LH neurons. Abstract: Early-life stress (ELS) has long-term consequences, including an increased risk for drug abuse and psychiatric disorders later in life, which is higher in women than in men. The consequences of ELS include heightened sensitivity to stressful events. Here, we hypothesized that ELS changes the stress sensitivity of dopaminergic (DAergic) neurons in the ventral tegmental area (VTA) and orexin (OXA) neurons in the lateral hypothalamus (LH), that are crucial for the control of motivated behaviors. We combined morphological and immunohistochemical approaches to investigate the effect of maternal separation (MS), a rodent model of the ELS, on the expression of c-Fos protein in putative DAergic and non-DAergic VTA and LH OXA neurons, as well as on dendritic spine density and morphology in the VTA of adult female rats. We showed that MS increased basal and acute restraint stress-induced c-Fos expression in putative DAergic neurons, specifically in the dorsomedial VTA, an area implicated in responsiveness to aversive stimuli. Conversely, restraint-induced increase in c-Fos expression in non-DAergic dorsolateral VTA neurons was dampened by MS. Furthermore, an increase in spine head diameter of VTA neurons and a concurrent decrease in dendritic spine density in dorsal VTA were observed. We also showed that MS changed the stress sensitivity of OXA neurons selectively in the dorsomedial hypothalamus (DMH), which is implicated in arousal and the stress response. These findings show the long-lasting consequences of ELS and indicate the selective, regional sensitivity of structures involved in the control of arousal, motivational behaviors and the stress response to ELS.